Review of research on female physical and psychological aggression - Edalati, Ali; Redzuan, Ma'rof; Mansor, Mariani; Abu Talib, Mansor (Canadian Center of Science and Education, 2010)
Several studies conducted on female aggression (physical and psychological) are the primary concern of the review done in this paper. This article contains three parts - the first part focuses on the findings which show that the rate of aggression for male and female are equal, while the second part focuses on the research that reveal the rate of physical aggression is higher in women than men. The third part concerns on studies which have shown higher level of psychological aggression in women compared to men. According to the existing literatures, the rate of female aggression is equal to those of men, and in some studies, the rates of physical and psychological aggression among women are found to be higher than among men. Thus, it is concluded that the rate of women aggression is not lower than men, but it is either equal to or higher than men.